A Meta-Analysis of Middle School Students’ Science Engagement - Aker, Leanna B.; Ellis, Arthur K. (International Dialogues on Education Journal, 2019)
The extent to which middle school students are engaged in required science courses is an elusive but increasingly documented phenomenon. Anecdotal and empirical evidence alike raise concern with a perceived decline in science engagement reported by students as they transition into the middle school setting. Even what it means to be engagé is not thoroughly agreed on. Though an agreed-on operational definition of engagement is still nascent, an emerging consensus on a three-faceted model of student engagement exists in the research literature (Fredricks, Blumenfeld, & Paris, 2004). Thus, a synthesis of existing primary research of early adolescents’ science engagement under this emerging conceptualization is warranted. The results of this meta-analysis indicate that instructional methods, class characteristics and competence predictors comprise the strongest relationship with self-reported science engagement in early adolescence. These predictors also show the strongest relationship with affective and cognitive engagement sub-types. Though affective and cognitive engagement were well-represented in primary studies, behavioral engagement was under-represented in student self-reports.